Ameliorative effect of gallic acid in doxorubicin-induced hepatotoxicity in wistar rats through antioxidant defense system (2017)
Hepatotoxicity has been found to be one of the main side effects associated with doxorubicin (Dox) administration in cancer therapy. The aim of the present study was to examine the ameliorative effect of gallic acid (GA) in Dox-induced hepatotoxicity. Sixty male Wistar rats of 10 rats per group were used in this study and were randomly divided into 6 experimental groups (A–F). Rats in Group A served as the control group and received distilled water orally for 7 days; Group B was given Dox at 15 mg/kg bodyweight intraperitoneally (IP) on Day 8. Group Cwas given GA at 60 mg/kg body weight orally for 7 days + Dox at 15 mg/kg IP on Day 8. Group D was given GA at 120 mg/kg body weight orally for 7 days +Dox at 15 mg/kg IP on day 8. Rats in Groups E and F were administered GA alone at 60 and 120 mg/kg bodyweight orally for 7 days, respectively. Dox administration led to a significant reduction in hepatic reduced glutathione and nonprotein thiol (NPT) together with significant increase in hepatic malondialdehyde, hydrogen peroxide generation, superoxide dismutase, and catalase activity; hepatic glutathione peroxidase and glutathione-S-transferase activity were significantly inhibited in Dox-treated rats. The serum alanine aminotransferase (ALT), alkaline phosphatase, and total bilirubin concentrations were significantly elevated following Dox administration. Pretreatment with GA ameliorated Dox-induced hepatotoxicity and oxidative stress. The results suggest that GA may offer protection against hepatic damage in Dox cancer chemotherapy.